Caffeine in preterm infants: where are we in 2020? - Moschino, Laura; Zivanovic, Sanja; Hartley, Caroline; Trevisanuto, Daniele; Baraldi, Eugenio; Roehr, Charles Christoph (ERJ open research, 2020)
The incidence of preterm birth is increasing, leading to a growing population with potential long-term pulmonary complications. Apnoea of prematurity (AOP) is one of the major challenges when treating preterm infants; it can lead to respiratory failure and the need for mechanical ventilation. Ventilating preterm infants can be associated with severe negative pulmonary and extrapulmonary outcomes, such as bronchopulmonary dysplasia (BPD), severe neurological impairment and death. Therefore, international guidelines favour non-invasive respiratory support. Strategies to improve the success rate of non-invasive ventilation in preterm infants include pharmacological treatment of AOP. Among the different pharmacological options, caffeine citrate is the current drug of choice. Caffeine is effective in reducing AOP and mechanical ventilation and enhances extubation success; it decreases the risk of BPD; and is associated with improved cognitive outcome at 2 years of age, and pulmonary function up to 11 years of age. The commonly prescribed dose (20 mg·kg −1 loading dose, 5–10 mg·kg −1 per day maintenance dose) is considered safe and effective. However, to date there is no commonly agreed standardised protocol on the optimal dosing and timing of caffeine therapy. Furthermore, despite the wide pharmacological safety profile of caffeine, the role of therapeutic drug monitoring in caffeine-treated preterm infants is still debated. This state-of-the-art review summarises the current knowledge of caffeine therapy in preterm infants and highlights some of the unresolved questions of AOP. We speculate that with increased understanding of caffeine and its metabolism, a more refined respiratory management of preterm infants is feasible, leading to an overall improvement in patient outcome.